2019
DOI: 10.1088/1748-9326/ab36fa
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the availability of bushmeat for consumption in Central African cities

Abstract: The trade of bushmeat from rural areas to supply burgeoning cities is a major conservation and livelihood concern. Using a whole-city sampling strategy we mapped the distribution and numbers of meat outlets in the Kinshasa-Brazzaville metropolitan area, two neighboring capital cities in Central Africa. We show that both cities differ in the number and density of meat outlets, with more in Brazzaville per area sampled and inhabitants. The number of meat outlets is related to human population densities and prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Two thirds of the Congo forest is located in the DRC; the basin is home to over 400 mammal species (CARPE, 2018). Kinshasa and Brazzaville were also chosen because they exemplify the wild meat trade in many parts of Africa with thriving and established wild meat cultures (Fa et al, 2019). Endangered species such as great apes ( Pan spp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two thirds of the Congo forest is located in the DRC; the basin is home to over 400 mammal species (CARPE, 2018). Kinshasa and Brazzaville were also chosen because they exemplify the wild meat trade in many parts of Africa with thriving and established wild meat cultures (Fa et al, 2019). Endangered species such as great apes ( Pan spp.…”
Section: Methodsmentioning
confidence: 99%
“…The restaurant and catering sectors are understudied groups in conservation, both with regards to the legal and illegal wild meat trade, despite indication that in some regions, up to half of consumers procure wild meat from local restaurants (Chausson et al, 2019). Fa et al (2019) randomly sampled restaurants in both Kinshasa and Brazzaville, and found that 24% of restaurants in both study areas sold wild meat to patrons. Restaurateurs are key actors between wild meat consumers and suppliers and thus play a central role in the supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…The overall consumption of wild meat in urban areas can be substantial and widespread, even if it makes up only a small proportion of per capita protein consumption (Wilkie et al 2005 ). For instance, in large urban centres like Kinshasa and Brazzaville (in the Democratic Republic of Congo and Republic of Congo respectively), a quarter of all restaurants offer wild meat for sale (Fa et al 2019 ). This wild meat can be transported long distances to urban markets (Bowen-Jones et al 2003 ), though it tends not to be part of the formal economy (Wilkie et al 2006 ).…”
Section: Wild Meat Dynamics Before and After Covid-19mentioning
confidence: 99%
“…There seems to be a huge discrepancy between what the law says and what the wildlife harvester, traders and consumers do. For example, hunting is not supposed to be allowed when the hunting season is closed (6 months/year), however, bushmeat is found in markets throughout the year across the country (Cronin et al, 2015; Fa et al, 2019; Hennessey & Rogers, 2008; Mbete et al, 2011) indicating that the “no hunting” rule is not enforced and/or not respected.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these efforts around protected areas, bushmeat consumption and commercialization in urban centers in general and in northern Congo appear to be increasing. Bushmeat is very common in the urban markets in the north of the Republic of Congo (Hennessey & Rogers, 2008; Poulsen, Clark, Mavah, & Elkan, 2009) and even in the urban centers of Brazzaville and Pointe Noire (Chausson, Rowcliffe, Escouflaire, Wieland, & Wright, 2019; Fa et al, 2019; Mbete et al, 2011) even when the hunting season is closed. This prompted our research.…”
Section: Introductionmentioning
confidence: 99%